The prognostic value of time from symptom onset to thrombolysis in patients with pulmonary embolism. (1st April 2022) - Keskin, Muhammed; Dogan, Selami; Kaya, Adnan; Tenekecioğlu, Erhan; Ocal, Lutfi; Cersit, Sinan; Seker, Mehmet; Yavuz, Samet; Orhan, Ahmet L.
Abstract: Background: According to clinical practice guidelines, thrombolysis can be administered during the 14 days after the beginning of symptoms in PE. However, the role of the early thrombolysis in PE has not been comprehensively investigated. In this study we evaluated the effect of short symptom-to-thrombolysis time (STT) in these patients who received the thrombolytic therapy within the 48-h. Method: A total of 456 patients with pulmonary embolism who underwent thrombolytic therapy in a tertiary center were included in the current study. The patients were stratified into three groups according to STT as: <12 h (Group 1), 12 to 24 h (Group 2) and > 24 to 48 h (Group 3). In-hospital events and long-term mortality were compared between the groups. Results: Group 3 had higher in-hospital mortality, acute kidney injury, cardiogenic shock, asystole, and the use mechanical ventilation and 3-year mortality compared to the other two groups. The 3-year overall survival for Group 1, 2 and 3 were 82.1%, 77.7% and 25.9% respectively. According to regression analysis, a STT > 24 h was independently associated with in-hospital and long-term mortality. Group 1 and 2 had similar in-hospital outcomes and long-term mortality. Conclusion: A short STT has a great importance in patients with PE who treated with thrombolytic therapy. The efficacy of systemic thrombolysis significantly drops after 24 h. Because of this situation, the period between the symptom onset and thrombolytic therapy should be kept short as much as possible. Highlights: Acute pulmonary embolism (PE) is one of the most devastating acute cardiovascular disorders and has a quite high risk of mortality. The association between the symptom period and the benefit of thrombolytics not clearly defined. Thrombolysis should be administered as soon as possible after the diagnosis of PE. The therapeutic window recommended by clinical guidelines for thrombolytic therapy in acute PE is unclear. Early administration of thrombolytic therapy is independently associated with in-hospital and long-term survival.